KEBIJAKAN PEMERINTAH DAERAH DALAM MENINGKATKAN KINERJA PELAYANAN KEBERSIHAN DI KOTA KEDIRI - Pujowati, Yenik (Universitas Wijaya Kusuma Surabaya, 2021)
This research aims to determine the performance of local government policies in improving solid waste services in the environmental cleanliness and gardening service of Kediri city. Based on Law No.18 of 2008 concerning waste management, regional regulation policy No. 3 of 2015 concerning waste management in Kediri City. Based on this regulation, it is very important to strengthen solid waste cleaning services in Kediri City. This research method used is a qualitative research method. Data is obtained through observation and analysis from secondary data and primary data. The results of this study indicate that the performance indicators of cleaning services on road sweeping are still less efficient and the technical work of road sweeping is still less productive, as a support for the infrastructure for waste collection equipment or waste collection from TPS / TPS 3R to TPA is still not optimal, this is due to limitations equipment in the environmental cleanliness and gardening service of Kediri City. From the results of the researchers, it can be concluded that the local government policy in improving the performance of cleaning services in Kediri City have not reached performance standards and the level of cleaning services cannot be said to be efficient and effective.Key Word: Public Policy Performance, Garbage Cleaning Services